Entre lo árabe y lo negro: raza e inmigración en Cartagena, 1880-1930 - Rhenals Doria, Ana Milena; Flórez Bolívar, Francisco (Sociedad y Economía, 2008)
This essay examines the historical circumstances which explain the articulation and acceptation of the sirio-libaneses, blacks and mulattoes groups to the cartagenera society in the transition from XIX to XX century.